JARGON VARIATIONS IN A COMMUNITY OF BEAUTY SALON WORKERS IN KECAMATAN KRONJO, BANTEN AND ITS IMPLICATIONS FOR LEARNING INDONESIAN LANGUAGE IN HIGH SCHOOL - Dwi Septiani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2023)
In the way of communicating, community contributors use a unique language in a jargon shape that is usually only understood through contributors of the community. Jargon is a variant of language that appears as the quit result of the intersection of social phenomena, social interactions, and approaches of speaking inside a community. The reason of this research is to describe the formation techniques and meanings of a number jargons in a community of splendor salon employees in Kecamatan Kronjo, Balaraja, Banten and their implications for mastering Indonesian in excessive school. Qualitative approach and descriptive technique are used in this research. Observations and documentation have been carried out in this study. Proficiency concerned commentary technique, free conversational engagement technique, recording technique, and notice taking approach have been also used to acquire data. Of the 50 statistics collected, the jargon used to be correctly recognized and classified. There are variations of the adjective jargon used in the Beauty Salon Worker Community in Kecamatan Kronjo, Balaraja, Banten, specifically 17 data, 12 records for nouns, and 11 statistics for verbs, pronouns as many as 6 data, adverbs are four data, and numerals are only 1 data. In addition, the jargon in the structure of a whole of 6 data. The consequences of this study on versions of jargon can be implicated for mastering Indonesian in excessive school, namely in primary competence 3.5, particularly writing anecdotal texts associated to the content and elements of implied meaning in anecdotal textual content material in classification X semester 1.